Expert Opinion and Compensation: Evidence from a Musical Competition - Ginsburgh, Victor A; van Ours, Jan C (American Economic Review, 2003)
Expert Opinion and Compensation: Evidence from a Musical Competition by Victor A. Ginsburgh and Jan C. van Ours. Published in volume 93, issue 1, pages 289-296 of American Economic Review, March 2003